THE IMPACT OF GOVERNMENT POLICY ON THE EFFECTIVENESS OF COMMUNITY EMPOWERMENT PROGRAMS - Istyaningrum, Nabila Astuti; Hanina, Naila (Bina Bangsa International Journal of Business and Management, 2025)
This research aims to critically examine various literature related to the impact of government policies on the effectiveness of community empowerment programs. Community empowerment programs have become an important instrument in socio-economic development, but their effectiveness is greatly influenced by the formulation and implementation of public policies. This study identifies that policies that are participatory, based on local needs, and supported by consistent regulations and adequate funding tend to have a positive impact on empowerment outcomes. On the other hand, a top-down approach without community involvement often results in unsustainable programs. The literature also highlights the importance of synergy between levels of government and implementing institutions to accelerate equitable empowerment. This study provides the implication that improvements in aspects of planning, coordination and policy evaluation can increase the effectiveness of empowerment programs in various local contexts.